The Relationship between Green Procurement Practices and Organizational Performance in the Manufacturing Industry of Vietnam - Tran Quyen (Arthatama, 2020)
Green procurement practices and management is one of the major elements that are adopted by various companies globally especially in the manufacturing industry to enhance the manufacturing sector to promote environment friendly practices. The research focuses on improving the manufacturing process via complying with the laws and regulations in the manufacturing department in Vietnamese companies. Deductive approach which is utilized in this approach is used for works with the practical reasoning and more practical ways to extract information. Questionnaire survey method is employed to carry out research method successfully. The survey was done to generate information as it is likely the most suitable way to collect reliable information from the mass target market. Research methodology section is important as this includes a variety of data collection approach, method and sample details that are significant for readers to understand. The findings show that there is a positive relationship overall between green procurement practices and organisational performance. Compliance with laws and regulations, and implementation costs have a significant impact on customer retention and sustainable performance. Contrarily, top management support and ICT have a significant impact on sustainable performance but insignificant on customer retention. Supplier selection, on the other hand, has a significant association with customer retention while insignificant association with sustainable performance. The study’s scope was limited to only manufacturing industry in Vietnam while mono-method of quantitative design was selected to carry out the study.